2022
DOI: 10.37990/medr.1096385
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Perceived Loneliness and Death Anxiety Levels in COVID-19 Patients

Abstract: Objective: The study was conducted to ınvestigation of perceived loneliness and death anxiety levels in COVID-19 patients. Materials and Methods: This cross-sectional and correlational study was carried out in XX Education and Research Hospital, located in southeastern Turkey, between January and April 2021. The population of the study consisted of patients who were diagnosed with COVID-19 over the age of 18. The sample of the study consisted of 152 patients who agreed to participate in the study at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Looking at the literature, many studies have revealed a positive and significant relationship between loneliness and death anxiety. 8,11,30 Kuru et al also emphasised the importance of addressing loneliness and death anxiety in a pilot study conducted on adults. 31 In addition, the mediating role of loneliness in the relationship between anxiety and death anxiety was investigated, shedding light on the interconnection of these psychological factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Looking at the literature, many studies have revealed a positive and significant relationship between loneliness and death anxiety. 8,11,30 Kuru et al also emphasised the importance of addressing loneliness and death anxiety in a pilot study conducted on adults. 31 In addition, the mediating role of loneliness in the relationship between anxiety and death anxiety was investigated, shedding light on the interconnection of these psychological factors.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it was found that death anxiety increased as loneliness increased ( P < 0.05). Looking at the literature, many studies have revealed a positive and significant relationship between loneliness and death anxiety 8,11,30 . Kuru et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The participants would experience a difficult time during isolation due to physical problems, loneliness, and separation from their families (Galehdar et al, 2020). A highly significant positive correlation existed between their loneliness and death anxiety (Buyukbayram et al, 2022). Moreover, the patients with COVID-19 experienced psychological distress, which increased six-fold from 9.6% to 72.5% (Thomas et al, 2021).…”
Section: Anxiety and Fear Of Dying Alonementioning
confidence: 99%